Bullying and its Implications on Middle School Students and Teachers in Indonesia - Charles Kapile; Nuraedah Nuraedah; Junarti Junarti; Fajar Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2023)
Bullying has happened in the diverse level of schools in Indonesia. This detrimental act certainly has a fatal impact on victims of bullying in the form of loss of confidence, social disability, worry, and possibly physical disturbances. The purpose of this study was to examine the implications of bullying for teachers and students at a junior high school in Indonesia, as well as the teacher's role in fighting bullying behaviour. This study uses a mixed method design with a non-probability sampling technique and quota sampling strategy. This study used questionnaires and interviews to gather information about bullying and the role of the teachers at that school in responding to such an act. The findings revealed two important issues as follows, a) Bullying of students is included in the mild criteria, namely 90.9% or 170 students, moderate, namely 8.0% or 15 students, and severe, namely 1.1%. or 2 students, and b) The teacher's role in preventing bullying is to provide supervision, guide, give advice and strengthen students' self-confidence so that they can overcome incidents or problems involving bullying to reduce bullying at school. This study indicates some implications regarding the preventive actions that school policy should apply to protect their pupils from experiencing bullying.